Increasing Cigarette Excise Tax Prevents Smoking Initiation in Children and Finances National Health Insurance in Indonesia - Purnamasari, Ayu Tyas; Pujiyanto, Pujiyanto; Thabrany, Hasbullah; Nurhasana, Renny; Satrya, Aryana; Dartanto, Teguh (UI Scholars Hub, 2018)
Indonesia has ranked third among countries with the highest number of smokers in Asia because the price of cigarettes in those countries is still affordable. The strategy to make the price of cigarettes is not affordable is increasing cigarette excise tax. This instrument is considered the most effective way to control cigarette consumption. The purpose of this study was to find out how the public perceive the increase of the cigarette excise tax to cover the National Health Insurance (NHI) deficit and to identify the factors which affect such perception. This study used mobile phone survey and the sample were 1000 respondents. The list of potential respondent’s mobile phone numbers was selected using the systematic random sampling method with an interval of 100,000 to 200,000. The result showed that 87.9% respondents agree to increase cigarette price so that the children do not start to smoke. The majority of respondents (86.2%) also agree to increase the price of cigarettes to finance the JKN deficit. Perceptions of respondents who agreed to increase the price of cigarettes to prevent smoking initiation in children also tended to accede the increase in cigarette prices for financing the JKN deficit.